Relationships Between Organizational Innovation Climate, Creative Self-Efficacy, and Innovation Performance: A Cross-Sectional Study in Public Hospitals. - Wu, Ruizhe; Feng, Xingmiao; Zhai, Ziyan; Sun, Xinyue; Wang, Zhen; Wang, Zhaoyang; Meng, Kai (Inquiry (00469580), 2026)
Physicians play a central role in medical innovation, bridging scientific discovery and clinical application. Underpinned by Social Cognitive Theory, this study examines the associations among organizational factors, psychological factors, and physician innovation performance, within the distinct setting of public hospitals. A cross-sectional survey was conducted among 1859 physicians from 22 tertiary municipal hospitals in Beijing. Multilevel structural equation modeling (MSEM) was employed to examine the relationships between organizational-level and individual-level variables. The hospital organizational innovation climate was positively associated with both physicians' creative self-efficacy (β =.255, P <.001) and their innovation performance (β =.501, P <.001). Creative self-efficacy was positively associated with innovation performance (β =.646, P <.001) and partially mediated the climate-performance relationship (indirect effect = 0.217). These results highlight the importance of the hospital innovation climate—integrated with robust resource systems and scientific incentives—as it relates to physicians' creative self-efficacy and their innovation performance in public healthcare institutions.